2011
DOI: 10.2478/v10172-011-0074-0
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Layered Mg/Eutectic Composite Using Diffusional Processes at the Mg-Al Interface

Abstract: A processing technique has been developed to produce a layered magnesium-intermetallic compound light composite from elemental magnesium and aluminium sheets. Structural examination and measurements of transition layer grown at the magnesium-aluminium interface at high annealing temperature were performed. It was found using Mg/Al diffusion couple that solid state diffusion results in development of Al 3 Mg 2 and Mg 17 Al 12 intermetallic compounds, which are separated into two sublayers. The rate of the layer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 18 publications
1
17
0
2
Order By: Relevance
“…No diffusion layer was observed to have been formed at the Mg-Al joint boundary in Al-Mg-Al sheets produced in either the symmetric or asymmetric rolling process. The rolling was conducted at a temperature lower than the eutectic temperature which, for the Mg-Al system, is 437°C [5,41,42]. the test results reported in study [41] demonstrate that it is possible to obtain a diffusion bond between the magnesium layer and the aluminium layer by soaking the package at a temperature of 430 o C for a duration of 20 minutes.…”
Section: Testing Results and Their Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…No diffusion layer was observed to have been formed at the Mg-Al joint boundary in Al-Mg-Al sheets produced in either the symmetric or asymmetric rolling process. The rolling was conducted at a temperature lower than the eutectic temperature which, for the Mg-Al system, is 437°C [5,41,42]. the test results reported in study [41] demonstrate that it is possible to obtain a diffusion bond between the magnesium layer and the aluminium layer by soaking the package at a temperature of 430 o C for a duration of 20 minutes.…”
Section: Testing Results and Their Analysismentioning
confidence: 99%
“…The rolling was conducted at a temperature lower than the eutectic temperature which, for the Mg-Al system, is 437°C [5,41,42]. the test results reported in study [41] demonstrate that it is possible to obtain a diffusion bond between the magnesium layer and the aluminium layer by soaking the package at a temperature of 430 o C for a duration of 20 minutes. In the study presented herein, the bond between the metals is of the adhesion type; the rolling temperature was too low for reactions to occur between magnesium and aluminium, as a result of which metallurgical bonding of individual layers in the strip would have been obtained.…”
Section: Testing Results and Their Analysismentioning
confidence: 99%
“…This indicates that the alloyed layers form during the solidification of the liquid layer, which appears at the interface between magnesium substrate and the Al-Zn powder mixture. In previous work [19] author and co-workers examined the layer growth, which was formed in elevated temperatures at the Mg-Al interface and reported that the rate of the layer growth substantially increases with the appearance of the liquid phase at the interface. Under experiment condition applied in a present work, addition of Zn into the diffusion powder mixture results in the formation of intermetallic phases that exhibit a low melting temperature below 437…”
Section: Resultsmentioning
confidence: 99%
“…Successful research on the joining of Mg with Al as well as the fabrication of Mg-Al compound parts is expected to further increase the application of these materials in lightweight structures. Different methods have been used to join these two types of materials, for instance, MIG welding [1], laser welding [2], friction stir welding [3], diffusion bonding [4,5], hot rolling [6,7], explosive cladding [8], twin-roll casting [9].…”
Section: Introductionmentioning
confidence: 99%